Assessment and Recognition of MOOCs: The State of the Art - Rob Farrow; Rebecca Ferguson; Martin Weller; Rebecca Pitt; Janesh Sanzgiri; Mustafa Habib (Journal of Innovation in Polytechnic Education)
Verification of learner identity is increasingly important for online education in examination and proctoring, and the Covid-19 pandemic has encouraged many institutions to move to online examinations at scale. This paper reviews state of the art approaches to ID verification, recognition and assessment in Massive Open Online Courses (MOOC). Desktop research included research publications, grey literature and MOOC platforms to identify current practices. The main focus was on public data from course pages on MOOC platforms, particularly courses that had been grouped to offer a single academic program, Four approaches are identified: basic ID checks, checks made by the university, proctoring and various types of interview.  Our review demonstrates the absence of any universal approach.  However, the emergent picture shows increasing co-ordination across relevant stakeholders (including higher education institutions, employment services and the private sector). Several more coordinated strategies (such as Europe’s Common Microcredential Framework) are highlighted. There remain significant challenges for online proctoring, including overcoming learner preferences and meeting the increased resourcing needed for human-led processes of identity verification. There remain significant ethical challenges regarding the use of learner data (especially biometrics).  MOOC platforms would likely benefit from adopting strategies that are well-established in higher education institutions such as plagiarism checking software and pedagogies like e-portfolios.